The relationship between toxic comment and the confidence of athletes’ coaching volleyball achievements - Adela Septi Purnama; Fina Nurunnisa Ma'muri; Abdul Aziz Purnomo Shidiq; ⁠Agus Kristiyanto; Rivan Adi Yohanda; Adela Septi Purnama; Fina Nurunnisa Ma'muri; Abdul Aziz Purnomo Shidiq; ⁠Agus Kristiyanto; Riva (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
Social media has become a part of athletes’ lives and can cause exposure to toxic comments that have an impact on psychological conditions, especially self-confidence. This study aims to determine the relationship between toxic comments on social media and the confidence of athletes coaching volleyball achievements at Sebelas Maret University. This study uses a quantitative, correlational method. The research subjects were 20 volleyball athletes enrolled in the achievement coaching program. Data were collected using toxic comments and confidence questionnaires, then analyzed using Pearson correlation tests and simple linear regression in IBM SPSS 25, after meeting the normality and linearity prerequisite tests. The results showed a significant negative relationship between toxic comments and athletes’ confidence (r = −0.520; p = 0.019) and a moderate relationship strength. The regression analysis showed that toxic comments accounted for 27.1% of athletes’ confidence. These findings indicate that the higher the exposure to toxic comments that athletes receive, the lower the level of confidence they have. Therefore, attention is needed to the psychological aspects of athletes, as well as efforts to strengthen digital literacy and mental resilience to foster sports achievements in the digital era.